LOCAL AND SYSTEM EFFECTS OF HYALURONIC ACID IMPLANTS IN CONDITIONS OF CORRECTIONS OF AGE-RELATED CHANGES IN SKIN - I. A. Khlusov; V. A. Igumnov; D. I. Choukhnova; O. L. Mytasova; K. V. Zaitsev; N. G. Abdulkina; A. A. Zaitsev; L. Yu. Kolesova (Бюллетень сибирской медицины, 2013)
Local and system influence the Repleri gel implants on the base of hyaluronic acid used to correct age-related changes in skin has been studied. Human stromal stem cells with CD44 membrane receptor to hyaluronic acid migrates in vitro into gel structure and maturates morphologically in fibroblast-like forms stained positively with acid phosphatase. Repleri gels implantation in the group of women with local and system age-related changes in homeostasis has positive local effect connected with full deletion of nasolabial fold in facial skin. Repleri gels injection has been decreasing during 1 year the system indices of real biological age as compared with chronological (passport) one. Lipoproteins and aspartate aminotransferase concentrations diminished statistically in women blood. An effect revealed may be considered as potential way of anti-age therapy of not only skin but parenchymal organs. At the same time, a long-term control of homeostasis distant indices in women with serious changes in parenchymal organs is necessary after local Repleri gels injection because of organism’s hormonal reactions.